Contemporary African fashion - Gott, Edith Suzanne; Loughran, Kristyne (African expressive cultures., 2010)
African fashion is as diverse and dynamic as the continent and the people who live there. This book puts Africa at the intersection of world cultures and globalized identities, displaying the powerful creative force and impact of newly emerging styles. Richly illustrated with color photographs, this book showcases haute couture for the African continent--[Book cover].